Pertobatan dan Pembaruan Budi: Studi Struktur Naratif atas Roma 12:1-2 dan Sastra Jendra Hayuningrat Pangruwating Diyu - Sugianto (Indonesian Journal of Theology, 2023)
Examining the harmony and disharmony between sacred texts and the wisdom tradition of the local community is an important step to develop a peaceful dialogue with the hope of reducing tensions, namely, in the social, cultural, and religious context of Java. In this study, the narrative structures of Romans 12:1-2 and Sastra Jendra Hayuningrat Pangruwating Diyu are placed in cross-textual dialogue. In particular, the author uses the actantial analytic reading method of Algirdas Julien Greimas to bridge an analysis concerning repentance and the renewal of the mind. This approach to cross-textual reading, as it is informed by Greimas' theory, focuses on the main narrative structure of Romans 12:1-2 and Sastra Jendra Hayuningrat Pangruwating Diyu, showing that there is both harmony that becomes the basis for dialogue but also disharmony that enriches the dialogue between these stories.